Whole-genome resequencing reveals the origin of tea in Lincang - Lei, Yahui; Yang, Ling; Duan, Shengchang; Ning, Siqi; Li, Dawei; Wang, Zijun; Xiang, Guisheng; Yang, Ling; Wang, Chunping; Zhang, Shiyu; Zhang, Shuangyan; Ye, Shuang; et al. (Frontiers in Plant Science, 2022)
Phylogeographic, population genetics and diversity analysis are crucial for local tea resource conservation and breeding programs. Lincang in Yunnan has been known as the possible place of domestication for tea worldwide, yet, its genetic makeup and unique Lincang origin are little understood. Here, we reported a large-scale whole-genome resequencing based population genomic analysis in eight main tea-producing areas of Lincang in Yunnan (1,350 accessions), and the first comprehensive map of tea genome variation in Lincang was constructed. Based on the population structure, tea sample in Lincang was divided into three subgroups, and inferred Xigui and Nahan Tea Mountain in Linxiang, Baiying Mountain Ancient Tea Garden in Yun, and Jinxiu Village of Xiaowan Town in Fengqing, which belong to the birthplace of the three subgroups, were all likely to be the origin center of Lincang tea. Meanwhile, the history population sizes analysis show that similar evolutionary patterns were observed for the three subgroups of Lincang. It also was observed that the hybrid among eight areas of Lincang was noticeable, resulting in insignificant genetic differentiation between geographical populations and low genetic diversity. The findings of this study clarified the genetic make-up and evolutionary traits of the local population of tea, which gave some insight into the development of Lincang tea.